Video game induced seizures. Issue 8 (August 1994) - Ferrie, C D; De Marco, P; Grünewald, R A; Giannakodimos, S; Panayiotopoulos, C P
Abstract : Fifteen patients who experienced epileptic seizures while playing video games are described together with a review of 20 cases in the English literature. Nine of the 15 cases and all but two of the reported cases experienced their first seizure while playing video games. Two thirds of patients had idiopathic generalised epilepsy and mainly reported generalised tonic clonic seizures, but some had typical absence seizures and myoclonic jerks while playing video games. In this series, 30% with idiopathic generalised epilepsy had juvenile myoclonic epilepsy. Overall, 70% of patients with idiopathic generalised epilepsy were photosensitive to intermittent photic stimulation and the mechanism of seizure provocation was probably similar to that of television induced seizures, although sensitivity to specific patterns was sometimes important. Two children had self induced video game seizures. Non-photic factors such as excitement, fatigue, sleep deprivation, cognitive processing, and diurnal variation in susceptibility seemed to be important seizure precipitants, particularly in non-photo-sensitive patients. Twenty nine per cent of patients had partial (mainly occipital) video game associated seizures. Occipital spikes were common in the EEG of these patients. Photosensitivity to intermittent photic stimulation may have been important in two patients but in the others, who all played arcade video games, other mechanisms need to be considered. Video game associated seizures are a feature of several epileptic syndromes and differ in precipitants and appropriate management.